ANALYSIS OF FACTORS THAT INFLUENCE THE FINANCIAL LITERACY OF MSME IN EAST BINJAI DISTRICT - Meutia Dewi; Suri Amilia (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
This research attempts to determine the factors that influence the financial literacy of MSMEs in East Binjai District, including gender, age, education level, and income level. This study had a population of 308 SMEs and a sample of 75 SMEs. Data collection methods are by distributing questionnaires and using measuring instruments like validity and reliability tests. The data analysis method used is descriptive analysis, multiple linear regression, t-test, F test and test the coefficient of determination. The results show that the financial literacy of MSMEs in East Binjai District is average in the medium category. The obtained multiple linear regression equation is Y = 2.431 + 0.037X1 – 0.222X2 + 0.338X3 + 0.271X4. The results of the t-test variable age, education level and income level have a significant effect, while gender has no significant impact. The results of the F test showed that the variables used in this study significantly affect the level of financial literacy. From the coefficient of determination test results, 82.6% was obtained, and the remaining 17.4% was influenced by other variables not examined in this study.